Study on ball milling duration effect of N-doped graphene for PEMFC application - Shu, Wen Oo; Sabli, Nordin; Siajam, Shamsul Izhar (Tamkang University, 2022)
Proton-exchange membrane fuel cell (PEMFC) requires a high-efficiency catalyst to overcome the sluggish oxygen reduction reaction (ORR) at the cathode side, thus N-doped graphene was introduced as an alternative catalyst. Ball milling is one of the approaches that is economical, scalable, and green to synthesize N-doped graphene. The ball milling parameters will greatly affect the quality of the synthesized N-doped graphene. Hence, this study aimed to access the ball milling duration effect on the synthesized N-doped graphene for the ORR improvement. N-doped graphene was synthesized through ball-milled graphite and melamine with different ball milling durations. The duration evaluated in this work was between 30 minutes to 50 hours. The results showed that the ball milling duration positively affects the ORR performance of N-doped graphene from 30 minutes to 12 hours. The best performance of N-doped graphene that synthesized through ball-milled 12 hours exhibits onset potential of -0.6 V and achieved almost four electrons transferred. This study concludes that ball milling duration significantly affects the quality of N-doped graphene for PEMFC but with an optimum duration, which is 12 hours.